On the expected value of uncertain variables - Zainab Hayder Abid AL-Aali (Al-Qadisiyah Journal of Pure Science, 2018)
In this work , some mathematical properties and several inequalities  for uncertain variables that based on uncertain measure and expected value are proved. Finally the relation between convergence in th moment and convergence in measure for uncertain sequence were investigated.